PENGARUH PENGGUNAAN JENIS IKAN YANG BERBEDA TERHADAP KUALITAS PEMPEK - Nofitasari, Neli; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
This research was designed for analyzing the effect of using different types of fish on the quality of Pempek in terms of froms, colors, flavors, textures, and taste. This research was classified into true experimental study which applied complete random sampling method. This research was conducted in three repetitions by involving 5 experts. The instrument of the research was a questionnaire of Likert scale. The data gathered through questionnaire were analyzed by using organoleptic test. To test the hypothesis, ANAVA was used, and if there was a difference occurred among the samples, Duncan test was needed. The result of the research revealed that the use of different fish affected the quality of Pempek in term of colors; golden yellow and white grayish, and in terms of texture which was chewy. Meanwhile the use of different types of fish did not influence the quality of pempek in terms of forms; cleanly, cylindrical, in the length of Â± 10 cm and diameter of 3 cm, in terms of flavors; garlic, fish, not fishy, in terms of texture which was soft, and in the terms of taste which was tasteful and fishy.Keyword: Fish, Pempek, and Quality.